Perancangan User Experience Aplikasi Android Konsultasi Skripsi dengan Metode User Centered Design - Rahmat Alif A.; Dedy Kurniawan (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
This research aims to design an Android application prototype using the User-Centered Design method, with a focus on evaluation through usability testing. The urgency of this research is driven by the importance of providing optimal user experiences in the development of Android applications, particularly in the context of thesis consultation applications, with the goal of enhancing user satisfaction and supporting business growth. The User-Centered Design method is employed as the primary approach in this research, involving steps such as user data collection, analysis, and iterative design based on user feedback. Usability testing is conducted through testing with users, aiming to identify issues and difficulties encountered by users while using the application. The usability testing process involved 5 participants, and the average test score obtained was 87.3. This test score indicates a very good level of usability. The results of this research are expected to provide valuable guidance for application developers in enhancing user experiences and better meeting user needs, ultimately achieving higher success.